2014
DOI: 10.1371/journal.pone.0092570
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Mismatching Expressive and Verbal Messages: A Contribution to Detection of Deception

Abstract: Processing facial emotion, especially mismatches between facial and verbal messages, is believed to be important in the detection of deception. For example, emotional leakage may accompany lying. Individuals with superior emotion perception abilities may then be more adept in detecting deception by identifying mismatch between facial and verbal messages. Two personal factors that may predict such abilities are female gender and high emotional intelligence (EI). However, evidence on the role of gender and EI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 70 publications
4
30
0
Order By: Relevance
“…No statistical differences were found here, only a trend for women to a better discrimination when judging a true statement and, interestingly, in the more difficult condition (neutral expression). This finding resembles the data of Wojciechowski et al (2014) about the superiority of women in the performance of a deception task with inconsistencies between the facial and verbal cues. It would be of worth for future studies to perform more experiments with larger samples to check if women can be better lie detectors than men in a variety of harder circumstances (for instance, in total absence of facial emotional cues).…”
Section: Discussionsupporting
confidence: 87%
“…No statistical differences were found here, only a trend for women to a better discrimination when judging a true statement and, interestingly, in the more difficult condition (neutral expression). This finding resembles the data of Wojciechowski et al (2014) about the superiority of women in the performance of a deception task with inconsistencies between the facial and verbal cues. It would be of worth for future studies to perform more experiments with larger samples to check if women can be better lie detectors than men in a variety of harder circumstances (for instance, in total absence of facial emotional cues).…”
Section: Discussionsupporting
confidence: 87%
“…DeBusk and Austin ( 2011 ), on the other hand, using the TEMINT, found that TEMINT was not a significant predictor of performance in the emotional IT task. In addition, Wojciechowski et al ( 2014 ) attempted to assess the emotional information processing of inconsistent signals through a facial-verbal decoding task (FDT). In these tasks, participants had to indicate if individuals who demonstrated a specific facial expression on the computer could have truthfully said particular sentences; participants were presented with congruent and incongruent trials.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results related to performance tests and hot cognitive tasks are promising, it is important to note a few limitations of the present study. First, some of the cognitive tasks may have methodological problems from being newly designed instruments whose reliability has not yet been probed; one example is the FDT (Wojciechowski et al, 2014 ). Second, we observed an enormous variety of instruments that were employed for measuring different aspects of cognition; specifically, 11 different hot cognitive tasks were related with EI performance tests.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy is considered necessary for social communication, predicting behavior, and the accurate identification of emotional cues (Keysers, 2012). Specifically, empathy relates to the accurate recognition of facial expressions (Besel & Yuille, 2010), even subliminally presented (Prochnow et al, 2013), and can aid the detection of mismatched emotions (Wojciechowski, Stolarski, & Matthews, 2014); all aspects underlying the EBA.…”
Section: Empathymentioning
confidence: 99%